Analysis of BRCA1 and mtDNA haplotypes and mtDNA polymorphism in familial breast cancer. (28th August 2013) - Gutiérrez Povedano, Cristina; Salgado, Josefa; Gil, Carmen; Robles, Maitane; Patiño-García, Ana; García-Foncillas, Jesús
Abstract: Mitochondrial DNA (mtDNA) defects have been postulated to play an important role in the modulation and/or progression of cancer. In the past decade, a wide spectrum of mtDNA variations have been suggested as potentially sensitive and specific biomarkers for several human cancer types. In this context, single nucleotide polymorphisms (SNPs) described as protective or risk variants have been published, in particular in breast cancer, though not without controversy. Moreover, many mtDNA haplogroups have been associated with different phenotypes and diseases. We genotyped 18 SNPs, 15 of them defining European mtDNA haplogroups, including SNPs described as protective or risk variants, 7 SNPs that determine BRCA1 haplotypes and a BRCA1 intron 7 polymorphism. We included in this study 90 Caucasian unrelated women with breast cancer with familial criteria and 96 controls. Our aim was to clarify the importance of any of these SNPs, mitochondrial haplogroups and BRCA1 haplotypes in the modulation of breast cancer. We detected no significant differences in the distribution of BRCA1 haplotypes between patients and controls. Haplogroup U and the 12308G variant of mtDNA were overrepresented within the control group ( p =  0.005 and p =  0.036, respectively) compared to breast cancer. Finally, we identified a significant association between the BRCA1 intron 7 polymorphism and BRCA1 haplotypes. Specifically, (TTC)6/6 and (TTC)6/7 genotypes with the seven polymorphic site cassette of "H2-like" haplotypes, and the (TTC)7/7 genotype associated with the "H1-like" haplotypes ( p  < 0.001).